Mucinous Adenocarcinoma of the Colon Presenting as a Psoas Abscess and Enterocutaneous Fistula: A Diagnostic Challenge (Mugda Medical College Journal, 2026)
Mucinous adenocarcinoma, also termed colloid carcinoma, represents a histological variant of colorectal cancer defined by extensive extracellular mucin production. It occurs slightly more often in females and tends to arise in the proximal colon. This uncommon malignancy may manifest with nonspecific or atypical clinical signs. We describe the case of a 37-year-old man, who presented with recurrent right-sided psoas abscesses and a discharging sinus, later complicated by the development of an enterocutaneous fistula. The definitive diagnosis of mucinous adenocarcinoma was established only after histopathological evaluation of the resected specimen. This case report emphasizes the diagnostic difficulty of atypical presentations of mucinous adenocarcinoma and underscores the need to consider an underlying malignancy in patients with recurrent or persistent abscesses.Mugda Med Coll J. 2026; 9(1): 95-98